2019
DOI: 10.15766/mep_2374-8265.10821
|View full text |Cite
|
Sign up to set email alerts
|

Constructing a Shared Mental Model for Feedback Conversations: Faculty Workshop Using Video Vignettes Developed by Residents

Abstract: Introduction Providing feedback is a fundamental principle in medical education; however, as educators, our community lacks the necessary skills to give meaningful, impactful feedback to those under our supervision. By improving our feedback-giving skills, we provide concrete ways for trainees to optimize their performance, ultimately leading to better patient care. Methods In this faculty development workshop, faculty groups used six feedback video vignettes scripted, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…27,138 While learner self-assessment may not correlate well with external assessments, 122,127,128 it can contribute positively to feedback discussions by encouraging reflection and establishing a shared understanding and mental model for feedback. 17,22,23,74,85,128,130,131,139 Combining self-assessment with feedback can positively impact improvement behaviors. 130,131 Importantly, while evaluative models for feedback have been shown to improve the number of feedback evaluations, they may not improve the quality of corrective feedback.…”
Section: Specialized Feedback Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…27,138 While learner self-assessment may not correlate well with external assessments, 122,127,128 it can contribute positively to feedback discussions by encouraging reflection and establishing a shared understanding and mental model for feedback. 17,22,23,74,85,128,130,131,139 Combining self-assessment with feedback can positively impact improvement behaviors. 130,131 Importantly, while evaluative models for feedback have been shown to improve the number of feedback evaluations, they may not improve the quality of corrective feedback.…”
Section: Specialized Feedback Techniquesmentioning
confidence: 99%
“…As a step toward improved performance, incorporating co-creation of goals 58 , 85 87 and the formation of learning or action plans into feedback can increase the benefit to trainees. 1 , 6 , 12 , 17 , 21 23 , 60 , 78 , 87 , 88 Additionally, encouraging collaborative discussion and learner reflection during the feedback conversation may be beneficial. 7 , 12 , 48 , 60 , 74 , 89 Faculty should be attentive and dedicated to providing feedback, as faculty effort and engagement have been shown to improve feedback.…”
Section: Giving Feedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to explore the intended meaning and breadth of the feedback construct, we completed the following steps in a pilot study [18]. We started by conducting a literature review that aligned the feedback construct with prior research and identified existing feedback scales.…”
Section: Related Researchmentioning
confidence: 99%
“…Faculty may be afraid to provide negative feedback 6,7 or just do not have time to give formative feedback. 15 Feedback curricula published previously in MedEdPORTAL have utilized video vignettes to train faculty to develop a shared mental model of feedback 16 or incorporated the use of a direct clinical observation tool. 17 Other published unidirectional feedback curricula have focused efforts on the learner, teaching recognition, solicitation, and utilization of constructive feedback.…”
Section: Introductionmentioning
confidence: 99%